Outpatient ADE (cytarabine, daunorubicin, and etoposide) is feasible and effective for the first relapse of pediatric acute myeloid leukemia: A prospective, phase II study. Issue 9 (16th July 2020) - Garg, Arun; Ganguly, Shuvadeep; Vishnubhatla, Sreenivas; Chopra, Anita; Bakhshi, Sameer
Abstract: Background: Approximately 40% children with acute myeloid leukemia (AML) invariably relapse, after attaining the first complete remission (CR), with dismal long‐term outcome. There is little consensus regarding choice of optimal induction chemotherapy regimen for relapsed pediatric AML. Procedure: A prospective single arm phase II study (CTRI/2017/02/007757) was carried out at our center to evaluate the safety and efficacy of outpatient cytarabine, daunorubicin, and etoposide (ADE) regimen in pediatric AML (≤18 years) at the first relapse. Response evaluation was done by bone marrow aspiration morphology along with minimal residual disease (MRD) assessment. All adverse events including need and duration of hospitalization, transfusion support, and antimicrobial use were recorded. Results: Total 45 patients were included with median age of 12 years. The CR rate of the cohort was 66% and 54% of patients were MRD negative. The estimated 2‐year event‐free survival (EFS) and overall survival (OS) were 29% (±7%) and 34% (±7%), respectively. The presence of fever at relapse was associated with inferior CR rate ( P  = .001), positive MRD ( P  = .01), and inferior EFS ( P  = .02), while not achieving nadir absolute neutrophil count of zero during induction was associated with inferior CR rate ( P  = .03) and inferior OS ( P  = .04). Approximately all patients developed ≥Grade 3 cytopenia and febrile neutropenia. Twenty‐six (59%) patients required hospitalization for management of toxicity and there were four (9%) deaths attributed to infection. Conclusion: ADE is an effective induction regimen for pediatric AML patients at the first relapse with reasonable toxicity profile. Outpatient administration of the regimen is feasible in the presence of proper support structure and rigorous follow up.